An organic route for the synthesis of cationic porous graphite nanomaterial used as photocatalyst and electrocatalyst for dye-sensitized solar cell. (10th March 2018) - Arbab, Alvira Ayoub; Mengal, Naveed; Sahito, Iftikhar Ali; Memon, Anam Ali; Jeong, Sung Hoon
Abstract: An organic synthesis route is proposed to fabricate cationized porous graphite (cpG) for photocatalyst and electrocatalyst nanomaterial. High crystalline structure of graphite possesses few defects and porous channels. In the proposed research, cpG is fabricated by sonicating graphite in cationized enzyme media followed by exfoliating in the activated charcoal filler. The cationic lipase solution distributed positive surface charges over a bare graphitic sheet, and sonication with activated charcoal filler divulges porous channels along graphite exfoliated matrix structure. The charcoal doping in graphite was modified with the different charcoal content percentage ranging from 0 to 100%. The cationized porous graphite (cpG) material possess high surface area, pore volume and conductivity leads to high photoresponse and electrocatalytic reaction. As photocatalyst, the proposed graphite provide fast degradation of methylene blue dye observed by UV–Vis spectrophotometer. As cathode for dye-sensitized solar cell (DSSCs), cpG provides high electrocatalytic activity with low charge transfer resistance (RCT  = 0.95Ω) and high photovoltaic performance with 9.59% efficiency. The positive charge distribution over graphite sheet attracts plenty of negative iodide ions present in the electrolyte, provide fast reduction-oxidation reaction. Furthermore, porous charcoal filler doping accepts a large amount of gel electrolyte, and fasten interfacial reaction between electrolyte and CE. This cost-effective cationized porous graphite (cpG) nanomaterial can provide new ways towards sustainable energy resources. Graphical abstract: Image 1 Highlights: An organic route for the synthesis of cationized porous graphite (cpG) nanomaterial is proposed. cpG used as photo catalyst and electro catalyst for DSSCs. cpG shows excellent degradation of methylene blue dye at very low time interval. cpG demonstrated low RCT of 0.95Ω with high photovoltaic performance. cpG cathode outperform Pt. electrode and exhibit 9.59% PCE of DSSCs.